Peningkatan Self Awareness Remaja Cegah Anemia melalui Program Structured Education Peer Counselor di Kota Denpasar - Agustini, Ni Komang Tri; Wahyuningsih, Luh Gde Nita Sri (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Background: The incidence of anemia among adolescent girls in Denpasar City was 45.9% and relatively high. Existing interventions were not optimal in reducing the incidence of anemia in adolescents. Increasing knowledge to increase self-awareness in adolescents can be done through empowering peer counselors by implementing the Structured Education Peer Counselor Program Objectives: to analyze the influence of Structured Education Peer Counselors on adolescent self-awareness in preventing anemia. Results: The research results showed that there was an influence of the Structured Education Peer Counselor Program on increasing teenagers' self-awareness to prevent anemia (p <0.001). Conclusion: This program was able to increase adolescent self-awareness in preventing anemia and can become input in developing appropriate educational programs for adolescents.